2018
DOI: 10.1016/j.chaos.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of epidemic spreading process in multi-communities

Abstract: a b s t r a c tIn practice, an epidemic might be spreading among multi-communities; while the communities are usually intra-connected. In this manuscript, each community is modeled as a multiplex network (i.e., virtual layer and physical one). The connections inside certain community are referred as inter-contacts while the intra-contacts denote the connections among communities. For the epidemic spreading process, the traditional susceptible-infected-recovered (SIR) model is adopted. Then, corresponding state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Mining the terrorist organizations for details is very useful. Various community detection algorithms can be applied [24].…”
Section: Applicationmentioning
confidence: 99%
“…Mining the terrorist organizations for details is very useful. Various community detection algorithms can be applied [24].…”
Section: Applicationmentioning
confidence: 99%
“…The third is the discrete probability model proposed by Wang in 2003 [29] . Models of disease spreading on more advanced networks, such as multilayer networks and adaptive networks, have also been investigated [30] , [31] . For example, Zhu et al proposed a two-layer network model to study the spreading properties of lethal diseases [32] .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Wang et al further found that the awareness inhibits the epidemic spreading, whereas the epidemic spreading facilitates the awareness diffusion [15]. Zhu et al thought that an epidemic might spread among multicommunities, so they modeled each community as a multiplex network that included both a virtual awareness layer and a physical layer [16]. ey further presented a coupled UAU-SIRD model, which consisted of a virtual layer sustaining unaware-aware-unaware dynamics and a physical layer supporting the susceptible-infected-recovered-dead process, to investigate the spreading property of epidemics and the relationships between the focused variables and parameters of the epidemic.…”
Section: Introductionmentioning
confidence: 99%
“…Some research studies assumed that the diffusion of awareness will reduce the infection rate of individuals [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%